X-FEM, de nouvelles frontières pour les éléments finis - Moës, Nicolas; Belytschko, Ted (European Journal of Computational Mechanics, 2002)
In 1999, an extension of the finite element method was introduced. Later called X-FEM (“eXtended Finite Element Method”), this extension allows one to model surfaces of discontinuity (cracks, material interfaces, free surfaces, . . . ) on a mesh even if the mesh does not conform to these surfaces. This paper summarizes the achievement obtained so far with XFEM, especially regarding the coupling of X-FEM with the “level sets” method which provides an efficient representation of the surfaces and a robust computation of their evolution.